Effect of the fullerene confining potential in the 1s → 2p resonant transition of H. (August 2015) - Frapiccini, A L; Gasaneo, G; Mitnik, D; Colavecchia, F D
Synopsis: In this work we study the effect of the confinement of H atom in a fullerene cage for the 1 s →2 p resonant transition of the atom interacting with a laser pulse. We present a novell implementation of the Generalized Sturmian Functions in the time-dependent frame to numerically solve this problem calculating the population of bound states and spectral density.